Peran Teknologi dalam Pembelajaran PAI: Analisis Efektivitas, Hambatan dan Solusi - Meisaroh, Tia; Mukti Nasrowi, Bagas (TAUJIH: Jurnal Pendidikan Islam, 2025)
This research aims to analyze the role of technology in Islamic Religious Education (PAI) learning and identify obstacles and solutions that can be implemented to enhance its effectiveness. The method used is a literature study, gathering data from various academic sources, including journals, articles, and research reports related to the use of technology in education. The study found that technology has significant potential to improve the quality of PAI learning through multimedia-based learning applications, e-learning platforms like Google Classroom or Moodle, and instructional videos accessible via YouTube or similar platforms. Additionally, augmented reality (AR) and virtual reality (VR) technologies can provide immersive learning experiences, such as Hajj simulations or Islamic history visualizations. However, the implementation of technology in PAI learning faces several, both physical and non-physical. Physical barriers include unequal access to ICT infrastructure, especially in remote areas, while non-physical barriers encompass educators' low technological proficiency, lack of confidence, and resistance to change. To address these challenges, this study recommends strategic solutions such as collaboration between educators and educational instit challenges utions, government funding for technological resources, continuous teacher training, and fostering harmonious relationships among educators, students, and parents. With these measures, the integration of technology into PAI learning is expected to support the achievement of Islamic education goals more optimally.